2015
DOI: 10.5539/ijbm.v10n9p1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Bank Efficiency and Its Determinants in Developing Countries Using Data Envelopment Analysis: The Case of Libya 2004-2010

Abstract: This paper offers to measure the technical efficiency and its determinants factors of Libyan Banks from 2004 to 2010. For this objective we use Data Envelopment Analysis for assessing technical efficiency in the first stage, and in the second stage we use the Tobit regression model to identify potential determinants of efficiency by using E-Views 7 software. The results showed that the specialized banks have exhibited higher mean technical efficiency relative to commercial and private banks. The results of eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…As a proxy variable for bank size, the estimations of ln_ta are significantly positive, which implies that the larger banks in China are more efficient. Similar results can be found in Reference [63]. Finally, all control variables are not significant, which indicates that macro-factors, such as market structure and GDP growth do not exert significant influence on bank efficiency; the same is true for other models.…”
Section: Determinants Of Bank Efficiency and Estimation Resultssupporting
confidence: 83%
“…As a proxy variable for bank size, the estimations of ln_ta are significantly positive, which implies that the larger banks in China are more efficient. Similar results can be found in Reference [63]. Finally, all control variables are not significant, which indicates that macro-factors, such as market structure and GDP growth do not exert significant influence on bank efficiency; the same is true for other models.…”
Section: Determinants Of Bank Efficiency and Estimation Resultssupporting
confidence: 83%
“…Findings from the study showed that reduction in inflation and rising GDP helped banks to perform more efficiently than otherwise. Khalad et al (2015) used the DEA and Tobit regression to examine the determinants of banks technical efficiency of specialized and private banks in Libya between 2004 and 2010. Findings from the study suggested that specialized banks were more technically.…”
Section: Determinants Of Bank Efficiencymentioning
confidence: 99%